Escin Chemosensitizes Human Pancreatic Cancer Cells and Inhibits the Nuclear Factor-kappaB Signaling Pathway - A. Rimmon; A. Vexler; L. Berkovich; G. Earon; I. Ron; S. Lev-Ari (Biochemistry Research International)
Background. There is an urgent need to develop new treatment strategies and drugs for pancreatic cancer that is highly resistant to radio-chemotherapy. Aesculus hippocastanum (the horse chestnut) known in Chinese medicine as a plant with anti-inflammatory, antiedema, antianalgesic, and antipyretic activities. The main active compound of this plant is Escin (C54H84O23). Objective. To evaluate the effect of Escin alone and combined with chemotherapy on pancreatic cancer cell survival and to unravel mechanism(s) of Escin anticancer activity. Methods. Cell survival was measured by XTT colorimetric assay. Synergistic effect of combined therapy was determined by CalcuSyn software. Cell cycle and induction of apoptosis were evaluated by FACS analysis. Expression of NF-κB-related proteins (p65, IκBα, and p-IκBα) and cyclin D was evaluated by western blot analysis. Results. Escin decreased the survival of pancreatic cancer cells with IC50 = 10–20 M. Escin combined with gemcitabine showed only additive effect, while its combination with cisplatin resulted in a significant synergistic cytotoxic effect in Panc-1 cells. High concentrations of Escin induced apoptosis and decreased NF-κB-related proteins and cyclin D expression. Conclusions. Escin decreased pancreatic cancer cell survival, induced apoptosis, and downregulated NF-κB signaling pathway. Moreover, Escin sensitized pancreatic cancer cells to chemotherapy. Further translational research is required.